Dampak Manajemen Pengelolan Risiko Terhadap Kinerja Keuangan Bank: Systematic Literature Review - Dita Hikmawaty Oktavia Ningrum; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the relationship between risk management and banking. It also examines the impact of credit risk management on bank financial performance. A Systematic Literature Review (SLR) is applied as the method in this study, which involves compiling scientific research articles from various journals relevant to the research topic. The results of several studies consistently show that the performance and financial stability of the banking sector are significantly influenced by several internal factors, such as financial risk management, operational efficiency, capitalization, and external factors such as economic conditions and technological advancements. Operational efficiency and cost management are crucial factors in increasing bank profitability. Therefore, bank management needs to improve risk management, strengthen capital, increase efficiency, and adapt to technological developments.